A case report on pregnancy with uncorrected tetralogy of Fallot with pulmonary hypertension managed uneventfully at a tertiary health care in India - Kumari, Gitanjali; Kakade, Aniket; Panchanadikar, Tushar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Tetralogy of Fallot (ToF) is the most frequent kind of cyanotic congenital heart disease beyond the age of one year, accounting for around 10% of all congenital heart disease cases. Natural (non-corrective) survival into the fourth decade is quite unusual (3 %). There are various physiological and heamodynamic changes that occur in pregnancy, which makes causes complications in pregnancy and delivery in already compromised women, including women with uncorrected ToF. ToF is still a major source of maternal morbidity (62%) and even fatality (10%) in ToF patients, and it has a considerable impact on foetal outcome. Discussed below a case of pregnancy in a 26-year-old woman with uncorrected ToF, was diagnosed to have pulmonary hypertension, was admitted for safe confinement. She was taken up for elective LSCS with due risk and was later shifted to ICU for further management.